Plio-Pleistocene Seismic Stratigraphy of the Java Sea between Bawean Island and East Java - Susilohadi Susilohadi; Tjoek Azis Soeprapto (Berita Sedimentologi, 2015)
The southeast Java Sea forms a submerged part of the Sunda Shelf and lies on a relatively stable continental shelf, which reached its final form during the Quaternary. Marine geological investigations in this area have mostly been carried out as part of regional studies on the Sunda Shelf. Detailed studies, particularly for younger sequences, are lacking and, as a result, the neo-tectonics and response of the shelf area to extreme sea level fluctuations during Plio-Quaternary times are poorly known.A set of high resolution reflection seismic profiles totalling some 3750 line km has been studied. All data were acquired by the Marine Geological Institute of Indonesia, which ran the survey in the southeast Java Sea in 1989-1990. The data show that the Late Tertiary sedimentation in the study area partly occurred in half graben basins, mostly bounded by northeastward trending faults which may be related to the regional suture belts running from central Java to south Kalimantan. Towards Pliocene time, the sedimentation occurred in east-trending synclinal basins, which indicate the dominance of a northward tectonic compressional stress. This continued until the Early Pleistocene, as indicated by some local thickening of the Early Pleistocene deposits. Since then, further basin development appears to have ceased, and a tectonically stable condition may have been reached. Quaternary sedimentation gradually changed the basin morphology into a relatively flat plain characterised by multiple erosional features resulting from extreme sea level fluctuations.